Pengaruh Kegiatan Mozaik dengan Bahan Alam Terhadap Kreativitas Anak Usia Dini - Astuti; Rusmayadi; Herlina (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research aims to determine the effect of mosaic activities with natural materials on the creativity of early childhood at Tunas Kasih Kindergarten, Makassar. The research approach used is a quantitative approach with a Quasi Experimental Design research type. Sampling in this research was purposive sampling. The population in this study was 39 children. The sample in this study consisted of 20 children, divided into 10 children as the experimental group and 10 children as the control group. Data collection techniques in this research include tests, observation and documentation. The data analysis techniques used are descriptive statistical analysis and non-parametric analysis. Based on the research results, it shows that it is -2.812 and the sig.(2tailed) value is 0.005 <0.05, so H0 is rejected and H1 is accepted. So it can be concluded that mosaic activities with natural materials have a significant influence on the creativity of early childhood at Tunas Kasih Kindergarten Makassar.